Early determinants of vagal activity at preschool age: with potential dependence on sex - Kühne, Britta; Genser, Bernd; Bock, Freia de (Early human development, 2016)
Background: In children, autonomic nervous function is related to various highly prevalent health problems and might therefore represent an early indicator of ill health. Aims: We aimed to investigate the role of early-life exposures and physical activity (PA) as potential determinants of autonomic function at preschool age. Study design and subjects: We used an existing longitudinal data set of repeated vagal tone measurements (assessed via heart rate recovery (HRR)) and retrospectively assessed early-life exposures in 1052 children (mean age: 59.4months, 47.5% girls) from 52 preschools in Germany recruited from 2008 to 2010. Outcome measures: HRR 1min after submaximal exercise served as primary outcome. Through multilevel linear regression analysis adjusted for demographic and socioeconomic factors, we assessed the association between repeatedly measured HRR and pregnancy smoking status, breastfeeding and objectively measured PA. Results: Besides significant regression coefficients for previously described correlates of HRR (sex, age), we could show positive associations of HRR with breastfeeding (six versus zero months: +4.2 beats per minute (BPM), p=0.004) and PA (+1.0BPM for 10min increase of moderate-to-vigorous PA/day, p<0.001). Smoking before and during pregnancy showed no significant association with HRR in the total sample. However, we found interactions between sex and smoking before and during pregnancy as well as between sex and breastfeeding, suggesting significant associations with HRR only in girls. Conclusions: Besides PA, early pre- and postnatal exposures seem to have long-lasting effects on children's autonomic function, still recordable at preschool age. Our data suggest that these effects might be sex-dependent.